PENGEMBANGAN VIDEO PEMBELAJARAN KONTEKSTUAL PADA MATERI ALAT-ALAT OPTIK (MATA, MIKROSKOP, DAN TELESKOP) DI SMA - Nur Faizah; Singgih Bektiarso; Sudarti Sudarti (FKIP Universitas Jember, 2019)
Abstract This study was conducted with the aim of describing the validity of contextual learning videos on the material of optical devices (eyes, microscopes, and telescopes) in high school and describing students' responses to the video using the response questionnaire. The method used in this research is research and development (Research and Development) by applying the Nieveen design to develop videos. Based on the results of the three stages of validation obtained an average validity for each aspect of the assessment of the validation of experts and users, namely, Relevance 87.5%, Accuracy of 93.75%, Contextual Learning 87.50%, and Linguistics 95%, so that a final validity of 90% is obtained with the category